if (x-1) is a factor of polynomial 3x2+2x-k
Answers
Answered by
5
zero of x-1 is 1.
so, p(x)=3x^2+2x-k
=>p(1)=3(1)^2+2(1)-k=0
=>p(1)=3+2-k=0
=>p(1)=5-k=0
so, 5-k=0
=>-k=-5
=>k=5
so, p(x)=3x^2+2x-k
=>p(1)=3(1)^2+2(1)-k=0
=>p(1)=3+2-k=0
=>p(1)=5-k=0
so, 5-k=0
=>-k=-5
=>k=5
kisalaya1:
please mark me brilliantest
Answered by
4
Heya user, Here is your answer
![given \: that \: (x - 1) \: is \: the \: factor \: of \: 3 {x}^{2} + 2x - k \\ so \: zero \: of \: x - 1 = 1 \\ therefore \: \\ p(1) = 0 \\ 3( {1)}^{2} + 2(1) - k = 0 \\ 3 + 2 - k = 0 \\ 5 - k = 0 \\ k = 5 given \: that \: (x - 1) \: is \: the \: factor \: of \: 3 {x}^{2} + 2x - k \\ so \: zero \: of \: x - 1 = 1 \\ therefore \: \\ p(1) = 0 \\ 3( {1)}^{2} + 2(1) - k = 0 \\ 3 + 2 - k = 0 \\ 5 - k = 0 \\ k = 5](https://tex.z-dn.net/?f=given+%5C%3A+that+%5C%3A+%28x+-+1%29+%5C%3A+is+%5C%3A+the+%5C%3A+factor+%5C%3A+of+%5C%3A+3+%7Bx%7D%5E%7B2%7D++%2B+2x+-+k+%5C%5C+so+%5C%3A+zero+%5C%3A+of+%5C%3A+x+-+1+%3D+1+%5C%5C+therefore+%5C%3A++%5C%5C+p%281%29+%3D+0+%5C%5C+3%28+%7B1%29%7D%5E%7B2%7D++%2B+2%281%29+-+k+%3D+0+%5C%5C+3+%2B+2+-+k+%3D+0+%5C%5C+5+-+k+%3D+0+%5C%5C+k+%3D+5)
Hope it will help you
Hope it will help you
Similar questions